O37 Preparation-for-practice: a pilot of blended simulation for new doctors. (31st December 2017) - Stallard, MJ; Chu, C; Gilfillan, P
Abstract : New Foundation Year one (FY1) doctors have commented on training deficiencies in several areas, including prescribing, decision making, treatment planning, prioritisation, team working and competence in carrying out clinical procedures [Cameron et al., 2014]. In recent years, many universities have introduced "Preparation for Practice" shadowing programmes to improve student readiness for their new role. The shadowing at our district general hospital occurs during "normal" working hours, potentially neglecting one of the most important parts of their practice; on-call shifts. We devised a pilot half-day course to simulate an on-call shift for final year undergraduates, as part of their Preparation for Practice programme. We began with a handover from existing FY1s of outstanding tasks and patient reviews. Our simulation centre was divided into stations and wards with various tasks – prescribing stations (fluids, warfarin, gentamicin, vancomycin and blood), cannulation, falls review, verification of death, and a patient review. There were a mixture of paperwork-only stations, part-task trainers, and mannequin-based simulation (a switched-off mannequin makes a very effective model for verification of patient death). During the session students were paged to attend for different tasks, and at intervals to review an acutely unwell patient, with the intention that they would prioritise them. This was a fifteen minute high-fidelity simulation, before senior help arrived to take over care. Students were allowed to attend stations at their own priority, and not in a standard OSCE carrousel. After each task, except for the acute patient review, students debriefed with a tutor. At the end of the session, students would perform a handover back to the original FY1, passing on any outstanding jobs. An overall debrief followed, with discussion about effective handover, multi-tasking, prioritisation, dealing with bleeps and prescribing. Feedback was overwhelmingly positive. One student described it as "the best thing she had done at medical school". Confidence scores for students at the start and end improved for all aspects. We believe this was a successful pilot and a valuable method of teaching. Improving the readiness of medical students to make the transition to unsupervised medical practice is difficult and we are heartened by the response of our learners. It is resource heavy in terms of faculty required, with each session accommodating four to five students, but is otherwise an efficient method of teaching a difficult subject in a safe environment. We believe there is potential to significantly expand this project. Reference: 1. Cameron A, Millar J, Szmidt N, Hanlon K, Cleland J. Can new doctors be prepared for practice? A review. The Clinical Teacher 2014;11:188–192. (John Wiley and Sons Ltd)